Natural spaces and the city, an approach from the ecological infrastructure in the surroundings of Chincha, Pisco and Ica cities - Medina Tarrillo, Gilmer (2018)
There is currently a growing interest in the natural spaces located on the periphery of cities, due to the environmental, social and economic benefits that they provide to citizens. This paper aims to evaluate the relationship between natural spaces and territorial planning instruments, considering the theoretical and methodological contributions developed from the ecological infrastructure.The methodology combines qualitative and quantitative tools, the qualitative were used for the analysis of the types and levels of use and also the natural spaces degradation, in addition, to determine the relevance of territorial planning instruments and the incorporation of the natural spaces in these. The quantitative variables were used to measure the relationship between variables, using a binary logistic regression. A total of 29 natural spaces and 13 planning instruments were registered and analyzed, the results explain qualitatively and quantitatively the poor incorporation of natural spaces in the planning instruments.